Fiscal justice in Brazil: Pathways to progress - Luana Passos; Dyeggo Rocha Guedes; Fernando Gaiger Silveira (International Policy Centre for Inclusive Growth (IPC-IG), 2019)
The purpose of this paper is to clarify the debate around the importance of fiscal justice in the promotion of equity and possible pathways to achieve it. To that end, the study included an analysis of the Brazilian tax system and of the existing literature on its distributive role and its efficiency. The findings point to inefficient taxation that is still very unequal, but with clear room for improvement. To increase efficiency and promote economic growth, we propose a change in the taxation of goods and services through the creation of a value-added tax (VAT) and changes in payroll so as to make it tax-exempt. Five pathways are suggested to improve fiscal injustice: a reduction of indirect taxation; changes to the rates and thresholds for personal income tax; the reintroduction of taxation of profits and dividends; the institution of a tax on large fortunes; and an increase in social spending. The current fiscal and economic crisis in Brazil points to the need for fiscal reform under these terms to ensure both efficiency and equity.
Keywords: 330; fiscal justice; equity; taxation; efficiency